Robust Optical Frequency Comb Generation by Using a Three-Stage Optical Nonlinear Dynamic - Zhang, Yali; Liao, Shuxu; Wang, Guan; Yang, Ke; Zhang, Zhiyao; Zhang, Shangjian; Liu, Yong (Frontiers in Physics, 2021)
In this paper, we propose and investigate a novel scheme to generate optical frequency comb (OFC) by using a three-stage generator, which is based on optical-injection-induced dynamics cascaded by subharmonic electro-optic modulation and four wave mixing (FWM) effect. A primary seed OFC is rooted from the nonlinear dynamics in the optically injected semiconductor laser, and its performance is improved using a two-stage booster based on subharmonic electro-optic modulation and FWM effect. The comb spacing can be easily tuned through adjusting that of the primary seed OFC, or through electro-optic modulation by use of subharmonics with different orders. Moreover, it becomes stabilized because the phase relationship between comb teeth can be fixed in the process of subharmonic electro-optic modulation. Its optical spectrum continues to be broadened in the following FWM process. Finally, robust OFCs with comb spacing of 4GHz and comb teeth number of 23, and comb spacing of 5GHz, comb teeth number of 21 are experimentally demonstrated.